Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Pengetahuan Remaja Putri Tentang Dampak Pernikahan Dini - Ayu, Cempaka; Eka Vicky Yulivantina; Sri Kuswanti (Jurnal Kesehatan, 2024)
Indonesia is ranked 37th out of 158 countries with the highest rate of early marriage in the world, and the second highest in ASEAN. Teenage marriage can have a negative impact on various aspects of life. Health education, including reproductive health education, is an important foundation for creating a physically, mentally, socially and economically healthy society, including the Marriage Age Maturation program. This research uses a quantitative design with a quasi-experimental method (Quasi Experimental Design) and purposive sampling technique. The population consisted of 100 teenage girls in classes X and XI at SMAN 1 Sungailiat, Bangka Regency, with a sample of 67 people. The independent variable was adolescent reproductive health education, while the dependent variable was knowledge of the dangers of early marriage. The research instrument used a knowledge questionnaire and a game of snakes and ladders about the dangers of early marriage, which were distributed to respondents. The validity and reliability of the instrument were evaluated, while data analysis used SPSS V.27 with univariate methods to see the characteristics of respondents and bivariate using the Wilcoxon test. Research shows a significant increase in students' knowledge about the dangers of early marriage after receiving reproductive health education. After being given reproductive health education using the snakes and ladders method, students' knowledge has increased from an average score of 52.48 to 89. Wilcoxon testing obtained a p-value of 0.000 so it was concluded that there was an effect of reproductive health education on the knowledge of adolescent girls about the dangers of early marriage at SMAN 1 Sungailiat